Pengembangan Media Pop Up Book Digital Berbasis Discovery Learning untuk Meningkatkan Keterampilan Menulis Teks Deskripsi di Sekolah Dasar - Sriyanti, Atika; Muktadir, Abdul; Susanta, Agus (UNIB Press, 2025)
This research aims to create digital pop up book media based on discovery learning to improve descriptive text writing skills in elementary schools. The research was conducted at SDN 01 Central Bengkulu. This research is development research (Reseach and Development) with the ADDIE model. The research object is a digital pop up book learning media based on discovery learning in Indonesian language lessons, material for writing poetry description texts. The instruments used were feasibility test questionnaires and teacher and student response test questionnaires. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 presentation experts. User response testing was carried out on 23 class IV students and 1 class teacher at SDN 01 Central Bengkulu. Data analysis is used to determine the validity of learning media using cross tabulation and questionnaire distribution. The results of the learning media feasibility test by the validator were reviewed from the material, language and presentation aspects, the material feasibility was 0.70 (feasible criteria), the language feasibility results were 0.70 (feasible criteria) and the presentation feasibility results were 0.80 (very feasible criteria). The results of the learning media field test by conducting a pretest and posttest with the gain test results showing 23 students with a high gain criterion of 10 students with a percentage of 43.5%, then a medium criterion of 12 students with a percentage of 52.2%, then a low criterion of 1 student. with a percentage of 4.3%. Apart from that, the results of interviews with class IV teachers showed a positive response. In other words, the learning media used can improve students' descriptive text writing skills.